SQL Server 2012 fundamentals for the accidental DBA LiveLessons (Sneak Peek Video Training) - Johnson, Eric, 1978-; Safari eBooks ([S.l.] : Addison-Wesley/Pearson, 2013)
"SQL Server is installed behind many third party applications and behind Microsoft development tools such as Visual Studio. In today's IT workplace, system administrators and developers with no prior exposure or background, are increasingly responsible for working with and managing SQL Server. In order to take on the role of "accidental DBA", they need to understand the basics of relational databases and technologies such as indexing and stored procedures in order to effectively develop applications. This video will cover SQL Server from their perspectives and give them what they need to manage these instances."--Resource description page.
Title from title screen (viewed Oct. 11, 2013).
Presenter, Eric Johnson.
Keywords: SQL server; SQL (Computer program language); Client/server computing; Database management; Electronic books